PENEGAKAN HUKUM TERHADAP KEKERASAN SEKSUAL PADA ANAK DI KABUPATEN KUNINGAN - Sarip Hidayat; Iman Jalaludin Rifa’i; Gios Adhyaksa; Dewi Lestari (TAHKIM, 2023)
This paper discusses the protection and law enforcement of cases of sexual violence against children in Kuningan District. Kuningan Regency is one of the areas in West Java which has quite high cases of sexual violence against children. In an effort to provide protection and law enforcement for victims of sexual violence, the police and related institutions such as the Social Service and the Integrated Service Center for the Protection of Women and Children (P2TP2A) work together to provide assistance and protection to victims. In addition, the police also carried out investigative and investigative actions to find the perpetrators and process them legally.Keywords: protection, law enforcement, sexual violence, children